Enhanced biohydrogen yield and light conversion efficiency during photo-fermentation using immobilized photo-catalytic nano-particles. (June 2023) - Zhang, Zhiping; Fan, Xiaoni; Li, Dong; Li, Yameng; Zhang, Quanguo; Duan, Zhisai; Yang, Guang; Zhu, Shengnan; Zhang, Haorui; Yue, Jianzhi
Graphical abstract: Highlights: Nano-SnO2 and cell immobilization technology were applied to PFHP process. Immobilized cells produced more H2 than free cells. Nano-SnO2 addition could promote PFHP performance. The CHY increased by 18.54% with the addition of nano-SnO2 . The light conversion efficiency increased by 12.41% with nano-SnO2 addition. Abstract: Bacterial immobilization is a common method in anaerobic fermentation, since of the maintenance of high bacterial activity, insurance of high density microbial during continuous fermentation, and quick adaptability to the environment. While, the bio-hydrogen production capacity of immobilized photosynthetic bacteria (I-PSB) is seriously affected by the low light transfer efficiency. Hence, in this study, photo-catalytic nano-particles (PNPs) was added into the photo-fermentative bio-hydrogen production (PFHP) system, and its enhancement effects of bio-hydrogen production performance were investigated. Results showed that the maximum cumulative hydrogen yield (CHY) of I-PSB with 100 mg/L nano-SnO2 (154.33 ± 7.33 mL) addition was 18.54% and 33.06% higher than those of I-PSB without nano-SnO2 addition and control group (free cells), and the lag time was the shortest indicating a shorter cell arrest time, more cells and faster response. Maximum energy recovery efficiency and light conversion efficiency were also found to be increased by 18.5% and 12.4%, respectively.